The Complete Evacuation Rate of Two Different Single Dose Misoprostol Regimens for Termination of Missed Abortion - Yasemin Taşcı; Serdar Dilbaz; Berna Dilbaz; Ali Haberal (Medical Network, 2007)
OBJECTIVE: To compare the complete evacuation rate of two different single dose misoprostol regimens in termination of missed abortion within 24 hours. STUDY DESIGN: Hundred and one women with a diagnosis of missed abortion were randomized into two groups. Women in Group I received four tablets of misoprostol (800 mg) vaginally. In Group II, two tablets of misoprostol were administered vaginally simultaneously with two tablets taken orally. Women were evaluated by transvaginal sonography after the initiation of vaginal bleeding (primary visit) or in cases with no bleeding within 24 hours after the administration. In cases that had not completed the abortion at the primary visit, a surgical evacuation was performed. Mean expulsion time, clinical outcomes, side-effects, complications and any additional interventions required were analyzed in two groups. RESULTS: There was no statistically significant difference between the two groups in terms of age, number of previous pregnancies, the complete evacuation rate at the primary visit or mean expulsion time. The complete evacuation rate within 24 hours was 18% in Group I and 14% in Group II (p=0.38). The overall complete evacuation rate was 16% (n=16). There was a statistically significant difference between the groups for mean hemoglobin values before and after treatment (0.64 vs 0.62 respectively, p<0.05). CONCLUSION: With a single dose misoprostol regimen regardless of the route of administration, overall complete evacuation rate was low at the first follow-up visit.